Propuesta para la enseñanza en la modalidad e-learning en el aprendizaje de historia del bloque sexto: Neoliberalismo en América latina de tercero de BGU - Calderón Yépez, Rodrigo Anthony (2025)
This research aims to develop an e-learning teaching approach for history, specifically Neoliberalism in Latin America, aimed at third-year high school students. It is based on the need to modernize history teaching by incorporating digital tools that facilitate critical understanding and active student participation.The study develops an elearning approach to reinforce history learning in the sixth block: Neoliberalism in Latin America in the third year of high school. Using a mixed-methodological approach, surveys and interviews were conducted with teachers and students, identifying the main barriers to traditional teaching and the opportunities offered by e-learning.As a result, a pedagogical approach was designed that integrates interactive videos, dynamic slides, concept maps, and discussion forums to foster more meaningful learning. In addition, evaluation criteria based on rubrics and questionnaires are established to assess the effectiveness of the e-learning proposal in strengthening learning about neoliberalism.The study concludes that the e-learning proposal significantly contributes to strengthening the learning of third-year high school students. This digital strategy facilitates more dynamic and flexible access to content, allowing students to interact with the material autonomously and at their own pace.